The form of state administration during the Shaibani period - Moydinov Muhammadali (Periodica Journal, 2023)
This article provides information on the reforms implemented in the sphere of administration, the rise of science and culture, and the sources of the history of the Shaybanid dynasty during the years of Shaibani rule.
Keywords: Shaibanis; state administration